2000
DOI: 10.1074/jbc.m004610200
|View full text |Cite
|
Sign up to set email alerts
|

A High Affinity Fungal Nitrate Carrier with Two Transport Mechanisms

Abstract: We have expressed the CRNA high affinity nitrate transporter from Emericella (Aspergillus) nidulans in Xenopus oocytes and used electrophysiology to study its properties. This method was used because there are no convenient radiolabeled substrates for the transporter. Oocytes injected with crnA mRNA showed nitrate-, nitrite-, and chlorite-dependent currents. Although the gene was originally identified by chlorate selection there was no evidence for transport of this anion. The gene selection is explained by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 28 publications
4
40
0
Order By: Relevance
“…Glutamate transporters from the human brain have been shown previously to form dimers and trimers (17). There are now several examples of transporters that have dual affinity for their substrate and/or two mechanisms (13,19,21,35,55). Further investigation is needed to determine if this applies to PitB.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate transporters from the human brain have been shown previously to form dimers and trimers (17). There are now several examples of transporters that have dual affinity for their substrate and/or two mechanisms (13,19,21,35,55). Further investigation is needed to determine if this applies to PitB.…”
Section: Discussionmentioning
confidence: 99%
“…These include the ability of TbNrt2 to support high-affinity transport of nitrate and nitrite, but not chlorate ions. With the sole exception of A. nidulans NrtA assayed in Xenopus oocytes [5], the nitrite transport capacity of other fungal NTs has not, so far, been determined directly. However, the observation that growth on nitrite is not impaired in either an A. nidulans nrtA/ntrB double mutant [6], or in an N. crassa nit-10 mutant [9], has been taken as an indication that none of the above NTs is capable of nitrite transport.…”
Section: The Tbnrt2 Transportermentioning
confidence: 99%
“…A large group of NTs (nitrate transporters), from both prokaryotes and eukaryotes, belong to the MFS (major facilitator superfamily) and, specifically, to the NRT2 family of NT-encoding genes [1][2][3]. The most well characterized fungal members of this family are NrtA (formerly known as CrnA) and NrtB from Aspergillus nidulans [4][5][6] and Ynt1 from Hansenula polymorpha [7,8]. They share a similar membrane topology, in which two sets of six TM (transmembrane) helices, with an N IN C IN (N-terminus intracellular/C-terminus intracellular) orientation, are connected by a large cytosolic loop.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies on nitrate uptake in plants have identified nitrate transporters as mediators of the influx of chlorate, giving support to the use of 36 CIO { 3 as a radiotracer transport analogue for nitrate (Deane-Drummond & Glass, 1982;Ruiz-Cristin & Briskin, 1991). This view has been subsequently modified in the light of results obtained by studying the kinetics of chlorate absorption, and interactions between chlorate and nitrate in intact plants (Kosola & Bloom, 1996), and results from electrophysiological experiments with Xenopus oocytes expressing individual nitrate transporter genes (Zhou et al, 1998(Zhou et al, , 2000. Currently, it appears that the ability to transport chlorate or chlorite is restricted to some members of the proton-dependent oligopeptide transport (POT) family (Galván & Fernández, 2001).…”
Section: Introductionmentioning
confidence: 99%